An Evaluation Scale of Medical Services Quality Based on ＂Patients＇ Experience - 田常俊 田悦 张亮 (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
An evaluation scale of medical services quality was developed on the basis of ＂patients＇ experience＂. The questionnaires were developed by, among others, searching relevant literature, col- lecting well-established assessment scales, measuring patients＇ experience and satisfaction, brain-storming, literature analysis. Delphi method was adopted for expert consultation. Scale items were screened and revised. The key indexes were converted. Field surveys were conducted for testing the reliability and validity of the scale. Our modified evaluation scale for measuring medical services quality based on ＂patients＇ experience＂ included 6 dimensions （tangibility, reliability, responsiveness, assurance, empathy and continuity）, and 50 items. The novel scale based on ＂patients＇ experience＂ may better serve the purpose of assessin~ medical services quality.